PNGP : a social relationship based routing algorithm for pocket switched network - Barua, Rupa; Shadman, Shauvik; Chakrabarty, Amitabha (© 2016 IEEE, 2018)
This article was published in the IEEE Xplore [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICCITECHN.2016.7860162 The Journal's website is at: http://ieeexplore.ieee.org/document/7860162/